Study of Mechanical, Thermal and Barrier Properties of Biodegradable Polylactic acid-Polyethylene Glycol- Alumina Nanocomposite - Mohammed Noori, Farah Tariq; Abbas Ali, Nadia (Iraqi Journal of Science, 2023)
Tensile , thermal, and barrier properties of polylactide PLA-basednanocomposite films that were prepared by solvent casting method withpolyethylene glycol (PEG), and alumina were studied. PLA/PEG blend showeddecrease in tensile strength and Young modulus but increased in elongation inPLA/PEG and increased in crystalline of PLA but decrease in glass transitiontemperature with the increasing of PEG concentration . A nano blend composites ofPLA/PEG/alumina (50/50/4) when compared to PLA/PEG blend indicated thattensile strength , Young modulus and glass transition temperature (Tg) increasedwith adding alumina nano particles, concentration and barrier propertiesimprovement due to its nucleating and reinforcing function mineral when add nanoalumina to PLA/PEG blend . These results indicated that the incorporation of Al2O3enhanced the Oxygen barrier properties of the PLA.